Applying Ayittey’s Indigenous African Institutions to generate epistemic plurality in the curriculum - Oscar O. Eybers (Transformation in Higher Education, 2019)
Background: South Africa’s institutions of higher learning are currently experiencing a dispensation in which calls for curricula transformation and decolonisation reverberate. While the need for curricula evolution is generally accepted, there appears to be a lack of awareness of methodologies which are applicable to changing curricula. To this end the study proposed the incorporation of Ayittey’s text Indigenous African Institutions into mainstream curricula for the following reasons: It is a rich source of indigenous African knowledge and includes history and information which relate to all disciplinary faculties and their areas of teaching.